2016
DOI: 10.1007/s11060-016-2249-z
|View full text |Cite
|
Sign up to set email alerts
|

Primary pituitary lymphoma: an update of the literature

Abstract: Primary intracranial lymphomas (Weller et al. in Neuro Oncol 14(12):1481-1484, 2012) are an emerging disease and an isolated localization in the pituitary gland i.e. primary pituitary lymphoma (PPL) represents a rare condition. We present an update of the most recent evidence for PPL through a systematic review of the literature. A systematic literature review was conducted using PubMed database up to October 2015. The population was defined as immunocompetent patients with a pathologically confirmed diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(82 citation statements)
references
References 48 publications
5
65
0
Order By: Relevance
“…Mean age at diagnosis was 58.9 years (range 18-86 years), without gender difference (M: F=1:1). Analyzing epidemiological features, the mean age at diagnosis is in line with previous findings, as the peak of incidence was reported around the sixth decade of age (5,9). Regarding gender difference, the systematic review by Tarabay et al (5) reported a slight prevalence in female subjects, but the data were in contrast with those of the previous analysis by Giustina et al (9) that, however, included immunocompromised patients in their investigation.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Mean age at diagnosis was 58.9 years (range 18-86 years), without gender difference (M: F=1:1). Analyzing epidemiological features, the mean age at diagnosis is in line with previous findings, as the peak of incidence was reported around the sixth decade of age (5,9). Regarding gender difference, the systematic review by Tarabay et al (5) reported a slight prevalence in female subjects, but the data were in contrast with those of the previous analysis by Giustina et al (9) that, however, included immunocompromised patients in their investigation.…”
Section: Resultssupporting
confidence: 85%
“…Among tumours causing hypopituitarism, an emerging clinical entity is primary pituitary lymphoma (5). Although it is a rare disease in last years an increasing frequency of primary intracranial lymphoma has been described worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Central DI related to infundibular infiltration is highly associated with anterior pituitary deficiencies, which were also demonstrated in this patient. While malignancy may be the most common cause of infundibular thickening, with lymphoma being a frequent offender (22), there remains a paucity of cases in the literature of diffuse large B-cell lymphoma causing pituitary infundibular thickening and multiple pituitary deficiencies.…”
Section: Resultsmentioning
confidence: 99%
“…We reported a rare case of hypopituitarism in a patient with intravascular large B-cell lymphoma who after complete hematological remission, reversed hypopituitarism after more than two years (8). Anterior pituitary deficiencies are present in 70% of cases (most have panhypopituitarism), diabetes insipidus is frequent (in 36% of cases), unlike in pituitary adenomas (7). MRI usually shows diffusely enlarged pituitary gland with invasion of both cavernous sinuses mimicking a pituitary adenoma.…”
Section: Pituitary Lymphomamentioning
confidence: 95%
“…Recently published systematic review of primary sellar lymphoma reported a total of 33 cases of this isolated localization of lymphoma in the sella (7). The vast majority of CNS lymphomas are non-Hodgkin B-cell lymphomas.…”
Section: Pituitary Lymphomamentioning
confidence: 99%